Actions of mothers during breastfeeding problems - Vainauskaitė, Vilita; Stundžienė, Rasa (Slauga. Mokslas ir praktika, 2023)
Abstract. Breastfeeding provides many health benefits for infant and mothers. Breastfeeding problems that most women experience during the breastfeeding period influence the shorter duration of natural infant breastfeeding. It is important to help mothers solve breastfeeding problems to continue infant breastfeeding. The aim. Analyse mothers’ actions in case of breastfeeding problems. Methods. A quantitative scientific study was carried out using a questionnaire survey. Mothers who have infants from 6 months and children up to 2 years of age filled in the. 387 questionnaires were suitable for study data analysis. Mathematical and minimal statistical data analysis was carried out. Results and conclusions. More than two-thirds of the mothers in the study experienced breastfeeding problems. Sore/damaged nipples and breast engorgement were the most common problems. Many mothers looked for information related to breastfeeding in the media, and more than half sought help from healthcare professionals. A significant connection was found between breastfeeding problems and shorter duration of breastfeeding. Mothers’ knowledge about the benefits of breastfeeding, better financial situation and help from healthcare professionals had a significant impact on the duration of breastfeeding.